Evidence for humid conditions during the last glacial from leaf wax patterns in the loess–paleosol sequence El Paraíso, Central Spain. (2nd July 2016) - Schäfer, Imke K.; Bliedtner, Marcel; Wolf, Daniel; Faust, Dominik; Zech, Roland
Abstract: The Mediterranean region is affected by the first consequences of anthropogenic climate change and suffers from aridization and drought periods. Reconstructing past climate and environmental changes might help to put those consequences into context, identify underlying mechanisms and improve predictions. Here we present leaf wax analyses for the loess–paleosol sequence (LPS) from El Paraíso, located in Central Spain and a selection of plants growing there today. The long-chain n -alkanes in almost the whole LPS are characterized by the dominance of C29, C31 and C33, indicating the presence of grasses and drought-adapted tree species, such as Juniperus and Olea . However, samples correlated with marine isotope stage (MIS) 2 (∼29–14 ka) have higher abundances of C25, C27 and C29, which may signal the presence of less drought-adapted deciduous trees and more humid conditions. n -Alkanoic acid patterns can tentatively be interpreted to confirm these results, but are less robust, because more plant species are needed for comparison. Our findings and interpretation are in line with climate modelling studies that suggest a southward shift of the westerlies and storm tracks during MIS 2, with fluvial and lacustrine records, and with glacial refugia for temperate trees in southern Europe. Compound-specific isotope analyses will hopefully soon provide additional information about paleoclimatic and -hydrologic changes and help establish a more precise and robust age control.